2017
DOI: 10.1007/s10734-017-0168-3
|View full text |Cite
|
Sign up to set email alerts
|

The stifling silence around scholarly creativity in doctoral education: experiences of students and supervisors in four disciplines

Abstract: The demand for developing creativity among doctoral students is found in a number of educational policies all over the world. Yet, earlier studies on Swedish doctoral education suggest that doctoral students' creativity is not always encouraged. Based on a critical hermeneutic approach and cases in four different disciplines, the aim of this study was therefore (1) to explore different shapes of doctoral students' creativity in Swedish doctoral education and (2) to reveal and find possible explanations to some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
0
37
0
2
Order By: Relevance
“…It is concluded that investing in conditions that foster graduate creativity means drawing a flexible and interdisciplinary curriculum; encouraging inter-institutional exchanges in Brazil and abroad; encouraging flexible thinking in the classroom, avoiding dogmatic positions; and promoting a culture of recognition and valuation of creativity. As mentioned by Brodin (2018), believing in doctoral students' creative abilities and empowering them to fulfill their potential can be the next ruling academic agenda. "Then their scholarly creativity will find a voice, breaking through the silence in doctoral education" (Brodin, 2018, p.670).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that investing in conditions that foster graduate creativity means drawing a flexible and interdisciplinary curriculum; encouraging inter-institutional exchanges in Brazil and abroad; encouraging flexible thinking in the classroom, avoiding dogmatic positions; and promoting a culture of recognition and valuation of creativity. As mentioned by Brodin (2018), believing in doctoral students' creative abilities and empowering them to fulfill their potential can be the next ruling academic agenda. "Then their scholarly creativity will find a voice, breaking through the silence in doctoral education" (Brodin, 2018, p.670).…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review study conducted by Duhamel (2016), it was found that conservative teaching, inadequate time allocation for study, and devaluing creativity were barriers to creativity in nurse education programs. Brodin (2018) interviewed 14 dyads of students and supervisors from graduate programs regarding creativity in Swedish doctoral education. The results revealed that students' creativity was "encapsulated in silence" due to restriction by scholarly traditions, embodying the power of their supervisors, and unrequested in practice.…”
mentioning
confidence: 99%
“…The universities included in the survey were drawn randomly (with re-sampling once it was not possible to maintain the same survey procedure). The sample breakdown was as follows: Yerevan (32 students), Graz (32), Nice (75), Aachen (39), Budapest (62), Chapingo (59), Krakow (76), Coimbra (51), St. Gallen (37) and Kyiv (42). The study was conducted between March 2017 and October 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Insufficient development of creativity in universities is a problem which is often mentioned in the literature [37][38][39]. The role of creativity in the educational process is the subject of research, along with the academic and innovation dimensions of universities [40][41][42]. Clegg [40] perceives "creativity" as a life force or power and compares it to the Ancient Greek idea of Eros.…”
Section: Creativity In the Education Processmentioning
confidence: 99%
“…In terms of the dissertation, EPT faculty provide ongoing and supportive access for their dissertation students. Brodin (2018) supported the necessity for dissertation supervisors to not act as gatekeepers, but as a "valuable intellectual resources" (p. 671). The dissertation chairs in the EPT program embrace this notion closely by encouraging students to select research topics they are passionate about and also that benefit their personal and/or professional communities and impact social change.…”
Section: Scholarly Mentorshipmentioning
confidence: 99%